Electronic spin state of iron in lower mantle perovskite - Li, Jie (National Academy of Sciences, 2004)
The electronic spin state of iron in lower mantle perovskite is one of the fundamental parameters that governs the physics and chemistry of the most voluminous and massive shell in the Earth. We present experimental evidence for spin-pairing transition in aluminum-bearing silicate perovskite (Mg,Fe)(Si,Al)O(3) under the lower mantle pressures. Our results demonstrate that as pressure increases, iron in perovskite transforms gradually from the initial high-spin state toward the final low-spin state. At 100 GPa, both aluminum-free and aluminum-bearing samples exhibit a mixed spin state. The residual magnetic moment in the aluminum-bearing perovskite is significantly higher than that in its aluminum-free counterpart. The observed spin evolution with pressure can be explained by the presence of multiple iron species and the occurrence of partial spin-paring transitions in the perovskite. Pressure-induced spin-pairing transitions in the perovskite would have important bearing on the magnetic, thermoelastic, and transport properties of the lower mantle, and on the distribution of iron in the Earth's interior.